2006
DOI: 10.1074/jbc.m605827200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Steady-state β-Amyloid Levels in the Brain by Neprilysin and Endothelin-converting Enzyme but Not Angiotensin-converting Enzyme

Abstract: The deposition of ␤-amyloid in the brain is a pathological hallmark of Alzheimer disease (AD). Normally, the accumulation of ␤-amyloid is prevented in part by the activities of several degradative enzymes, including the endothelin-converting enzymes, neprilysin, insulin-degrading enzyme, and plasmin. Recent reports indicate that another metalloprotease, angiotensin-converting enzyme (ACE), can degrade ␤-amyloid in vitro and in cellular overexpression experiments. In addition, ACE gene variants are linked to AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
3
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(154 citation statements)
references
References 52 publications
8
135
3
1
Order By: Relevance
“…An acute, one-shot oral administration of captopril to the young Tg2576 mice resulted in a significant decrease in serum and brain ACE activities; however, the level of brain A␤ 1-42 or A␤ 1-40 was not significantly affected. A recent in vivo study also shows that ACE inhibitors at doses similar to those used clinically do not increase the levels of brain A␤s (Eckman et al, 2006). Previous studies using purified human seminal plasma ACE and cultured cells showed that ACE degrades A␤s and ACE inhibition increases A␤ levels in APP-and ACE-transfected cells (Hu et al, 2001;Hemming and Selkoe, 2005;Oba et al, 2005).…”
Section: Discussionmentioning
confidence: 88%
“…An acute, one-shot oral administration of captopril to the young Tg2576 mice resulted in a significant decrease in serum and brain ACE activities; however, the level of brain A␤ 1-42 or A␤ 1-40 was not significantly affected. A recent in vivo study also shows that ACE inhibitors at doses similar to those used clinically do not increase the levels of brain A␤s (Eckman et al, 2006). Previous studies using purified human seminal plasma ACE and cultured cells showed that ACE degrades A␤s and ACE inhibition increases A␤ levels in APP-and ACE-transfected cells (Hu et al, 2001;Hemming and Selkoe, 2005;Oba et al, 2005).…”
Section: Discussionmentioning
confidence: 88%
“…For brain A␤ ELISAs from 2-month-old Tg2576 mice, hemi-forebrains were homogenized in radioimmunoprecipitation assay buffer (0.1% SDS, 0.5% deoxycholate, 1% Triton X-100, 150 mM NaCl, and 50 mM Tris-HCl) and then ultracentrifuged at 100,000 ϫ g for 1 h. To measure the endogenous mouse A␤ levels, hemi-forebrains of nontransgenic littermates of the TgCRND8 mice expressing BRI2 were homogenized in 0.2% diethylamine buffer containing 50 mM NaCl and 1ϫ protease inhibitor mixture (Roche). Endogenous mouse A␤ levels were measured using the previously validated rodent-specific A␤ ELISA system as previously reported (Eckman et al, 2006). For plasma A␤ analysis, blood was collected in EDTA-coated tubes after cardiac puncture.…”
Section: Methodsmentioning
confidence: 99%
“…The ability to hydrolyze insulin is not shared by NEP which may makes a better candidate. NEP has been considered a promising candidate for AD treatment, since it appears to be the major, or one of the major enzymes involved in Aβ clearance in the brain [11,19,20,28]. NEP has other advantages over IDE and MP-1.…”
Section: Discussionmentioning
confidence: 99%